2002
DOI: 10.1067/mtc.2002.121497
|View full text |Cite
|
Sign up to set email alerts
|

How common is severe pulmonary hypertension after pediatric cardiac surgery?

Abstract: Severe postoperative pulmonary hypertension occurred after 2% of the cardiac procedures and in most cases was managed successfully with conventional treatment and had a favorable postoperative outcome. The low incidence relative to previous reports may reflect the benefits of early correction and improved intraoperative and postoperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 23 publications
2
109
0
8
Order By: Relevance
“…While the clinical impact of pre-and postoperative PHT has become considerably less threatening during the last decade, 13 there are some patients who develop marked postoperative PHT associated with hemodynamic compromise. Furthermore, subclinical elevation of PVRI may be associated with prolonged postoperative recovery.…”
Section: Clinical Impact Of Increased Pvr In Children With Congenitalmentioning
confidence: 99%
“…While the clinical impact of pre-and postoperative PHT has become considerably less threatening during the last decade, 13 there are some patients who develop marked postoperative PHT associated with hemodynamic compromise. Furthermore, subclinical elevation of PVRI may be associated with prolonged postoperative recovery.…”
Section: Clinical Impact Of Increased Pvr In Children With Congenitalmentioning
confidence: 99%
“…[10][11][12] Prevention and management strategies for pulmonary hypertensive crises include intraoperative vertical vein opening, deep sedation, muscle paralysis for 24-48 hours, maintaining the pCO 2 between 30 and 35 mmHg, pharmacological therapy (e.g., sildenafil, phenoxybenzamine, ilioprost, and iNO), the use of a selective pulmonary vasodilator, and ECMO life support. [10][11][12] Karaci et al [9] reported that 10% of the patients (n=6) in their study with isolated TAPVR had a pulmonary hypertensive crisis and that in spite of intensive therapy, two of them died. In another study composed of 100 patients, Kelle et al [12] observed a pulmonary hypertensive crisis in 20 patients, and three of these died as a result of the crisis.…”
Section: Discussionmentioning
confidence: 99%
“…É uma alteração verificada nos pós-operatórios de crianças que já tinham pressão pulmonar aumentada previamente (acima da metade ou 2/3 da pressão sistêmica) ou que tinham cardiopatias com grande shunt esquerda-direita 17 . Outros fatores como dor, agitação, acidose, hipercapnia e aspirações traqueais podem aumentar a pressão pulmonar.…”
Section: Hipertensão Pulmonarunclassified